MENJAGA REPUTASI DI TENGAH BENCANA : ANALISIS KOMUNIKASI KRISIS PT KAI PASCA ANJLOKNYA ARGO BROMO ANGGREK - Uly Wali Daturrahmah; Vidya Citra Ramadhita; Tria Patrianti (PT. Hasba Edukasi Mandiri, 2026)
This study analyzes the crisis communication strategy of PT Kereta Api Indonesia (Persero) in handling the derailment of the Argo Bromo Anggrek train on August 1, 2025, in Subang, West Java. The incident, which resulted in five carriages derailing, 80 train journeys canceled, and 42 journeys diverted, became a severe test for PT KAI's reputation and public trust. Using a qualitative case study approach, this research analyzes official documents, media coverage, and relevant literature to identify the crisis communication strategies implemented. The analytical framework employs Coombs' Situational Crisis Communication Theory (SCCT) and Benoit's Image Repair Theory. The findings reveal that PT KAI implemented a structured three-stage crisis communication strategy: pre-crisis through zero accident principles and CSR programs; during crisis through rapid response, empathy, transparency, stakeholder collaboration, and concrete actions including 100% refunds; and post-crisis through evaluation and system improvement. Based on SCCT, this incident is categorized as an accidental cluster with effective diminish and rebuild strategies. This study concludes that consistent messaging integration, digital sentiment monitoring, and balancing technical explanations with empathy were key factors in PT KAI's successful crisis communication in restoring public trust. This research recommends strengthening digital communication strategies and conducting periodic communication audits to enhance future crisis management effectiveness.